KEDUDUKAN SERTIFIKAT HAK CIPTA SEBAGAI JAMINAN KREDIT (STUDI KOMPARATIF ANTARA INDONESIA DENGAN SINGAPURA) - Ruhtiani, Maya; Afriliani Putri , Rizka; Hafny Afrilies, Marlia (J-LEE - Journal of Law, English, and Economics, 2025)
This research is entitled “The Legal Status of Copyright Certificate as Loan Collateral (A Comparative Study between Indonesia and Singapore)”, aiming to analyze and compare the legal regulation and protection of copyright certificates as loan collateral in Indonesia and Singapore. This study employs a normative juridical method with statutory and comparative approaches. The findings reveal that both Indonesia and Singapore recognize copyright as a viable collateral object. However, Singapore has established a more structured system through the Copyright Act 2021, the IP Financing Scheme, and the Intellectual Property Office of Singapore (IPOS), which facilitates the monetization of copyright with standardized valuation methods. In contrast, Indonesia, despite having a legal basis through the Copyright Law, Fiduciary Law, and Government Regulation No. 24 of 2022, still faces practical barriers such as the absence of a dedicated financing scheme, lack of standardized valuation, and minimal involvement from financial institutions. Therefore, legal and policy reforms are needed in Indonesia to strengthen copyright as an economic asset that can be effectively used as loan collateral.